Cross-Section Strength of Circular Concrete-Filled Steel Tube Beam-Columns - Denavit, Mark D.; Hajjar, Jerome F.; Leon, Roberto T. (Engineering Journal, 2016)
Closed-form expressions for the cross-section strength of steel-concrete composite beam-columns according to the plastic stress distribution method are tabulated in the AISC Seismic Design Manual and the AISC Design Examples. Approximations have been used in the deriva- tion of these formulas, most of which do not significantly affect the accuracy of the results. However, an approximation in the equation for the axial strength of circular, concrete-filled steel tubes that are simultaneously subjected to flexure at one of the key points on the interaction curve (designated as Point E) leads to results that are unconservative. The derivation of the equation is reviewed and a more accurate expression is proposed.